Immediate Loading of Dental Implants with Fixed Prosthodontic Constructions Advantages and Methods - Dolidze, Tamar; Kublashvili, Marika (European Scientific Journal, ESJ, 2022)
“Immediate loading of implants” implies loading of implants after extraction of a tooth. The goal of our study was to observe the loss of keratinized gums and bone tissue in the region surrounding the alveolar ridge after tooth extraction, and to compare it to the immediate loading of dental implants with the same indicator. Recently, immediate implant placement after the extraction of a tooth with early loading has become more common. The advantages of this procedure include fewer surgical interventions, reduction in overall treatment time, reduced soft and hard tissue loss, and psychological satisfaction for the patient. This study shows the advantages and methods for immediate implant placement with immediate provisional restorations.